Agenesis of mandibular second premolar in patient with dental bimaxillary protrusion - Carlos Alberto Estevanell Tavares
ABSTRACT The present study reports the treatment carried out in a patient with mandibular second premolar agenesis associated with early loss of a deciduous second molar, deep overbite, severe overjet and dentoalveolar bimaxillary protrusion, which led to lip incompetence and a convex facial profile. The main objectives of this treatment were: to eliminate the spaces in mandibular arch, correct overbite, as well as eliminate bimaxillary protrusion and lip incompetence, thus leading to a balanced profile. The case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as part of the requirements to obtain the title of BBO diplomate.